An Analysis Types of Onomatopoeia Words in Batman Beyond Comic - Didi Prihadi; I Gusti Agung Sri Rwa Jayantini; I Wayan Resen (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2021)
Language is very important for every people, by using language people can communicate with each other in daily life. There are a lot of studies that discuss language and one of them is onomatopoeia. Onomatopoeia is naming objects or actions based on the imitation of sounds associated with the object or actions. It can be divided into five types; Mechanical Onomatopoeia, Fast Motion Onomatopoeia, Musical Onomatopoeia, Fighting Onomatopoeia, and Animals Onomatopoeia. The article entitled “An Analysis Types of Onomatopoeia Words in Batman Beyond Comic, aims to identify the types of onomatopoeic words are found in Batman Beyond comic. To analyze the data, the main theory used in this article is the theory of onomatopoeia proposed by Marry Elizabeth. This research used a descriptive qualitative method to present the data descriptively and qualitatively to support the data found in Batman Beyond. The result of this study shows the types of onomatopoeic which include Mechanical, Fast Motion, Musical, and Fighting Onomatopoeic. From 56 data found in the Batman Beyond Comic, the types of fighting onomatopoeic are most commonly occurring with 26 data and followed by the mechanical onomatopoeic with 17 data, and the fast motion with 12 data.